Multifocal Anaplastic Pancreatic Carcinoma Requiring Neoadjuvant Chemotherapy and Total Pancreatectomy: Report of a Case - Jones, Teresa S; Jones, Edward L; McManus, Martine; Shah, Raj; Gajdos, Csaba (JOP. Journal of the Pancreas, 2013)
Context Anaplastic pancreatic carcinoma is a rare tumor with poor survival. Data on surgical and medical therapies are currently limited to case reports and case series with small numbers. Case report We describe a case of multifocal anaplastic pancreatic carcinoma treated with neoadjuvant FOLFIRINOX (oxaliplatin, irinotecan, fluorouracil and leucovorin) and total pancreatectomy with subsequent patient disease-free survival currently at 12 months. Discussion The goal for anaplastic pancreatic carcinoma treatment should continue to be complete surgical resection. Optimum chemotherapeutic options continue to be investigated. Image: Foreign body giant cells.